PENGARUH PENGALAMAN AUDITOR TEKANAN KETAATAN DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT - Dwi Ratna Ayu Puspitasari; Yuli Chomsatu; Riana R Dewi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The purpose of this study is to examine the effect of profitability, solvency, liquidity, company size and audit opinion on the company's audit report lag. Researchers used 31 banking companies listed on the Indonesia Stock Exchange for the period of 2014-2017 from audited banking companies. Test result 1 shows profitability has an effect on the company's audit report lag, while solvency, liquidity, company size and audit opinion have no effect on the company's audit report lag. Adding insight and knowledge about accounting knowledge, especially in understanding the effect of profitability, solvency, liquidity, company size, audit opinion on Audit Report Lag in analyzing each information so that the information can be useful in increasing student knowledge of the company's audit field and this research is expected to provide useful information for consideration of policy making in order to improve company performance to be more productive and efficient.